Incorporation of Europium in Bi2Te3Topological Insulator Epitaxial Films - Fornari, Celso; Bentmann, Hendrik; Morelhao, Sergio L.; Peixoto, Thiago R. F.; Rappl, Paulo H. O.; Tcakaev, Abdul-Vakhab; Zabolotnyy, Volodymyr; Kamp, Martin; Lee, Tien-Lin; Min, Chul-Hee; Kagerer, Philipp; Vidal, Raphael C.; et al. (Journal of Physical Chemistry C, 2020)
In the field of topological materials, the interaction between band topology and magnetism remains a current frontier for the advancement of new topological states and spintronic functionalities. Doping with rare-earth elements with large magnetic moments is a current approach to exploit the phenomenology of such interaction. However, dopant solubility into the main matrix plays a major role. In this sense, the present work is focused on elucidating how Eu incorporates into Bi2Te3 lattice as a function of doping. This work reports a systematic investigation of the structural and electronic properties of bismuth telluride epitaxial layers doped with Eu. Bi2Te3 films were grown by molecular beam epitaxy on (111) BaF2 substrates with nominal Eu doping ranging from 0% up to 9%. X-ray diffraction analysis and scanning transmission electron microscopy reveal that Eu atoms enter substitutionally on Bi sites up to 4% of Eu doping. In contrast, the 9% Eu-doped sample contains epitaxially oriented nanoclusters of EuTe. X-ray photoelectron and absorption spectroscopies show that Eu atoms enter the Bi2Te3 crystal matrix in the divalent Eu2+ state for all Eu concentrations. Angle-resolved photoemission experiments indicate that the topological surface state is preserved in the presence of the local magnetic moments introduced by the Eu impurities.
CRIS-Team Scopus Importer:2022-04-14